Strength and behaviour of optimised channel shaped polymer modified ferrocement flexural elements - Sheela, S (Journal of Structural Engineering, 2024)
Ferrocement is a versatile concrete composite material highly suitable for low cost housing. Ferrocement have several applications in building industry such as roofing and flooring element, other building elements like doors, lintels and construction of ferrocement water tanks, boats, etc, because of its durability, cost effectiveness and superior cracking resistance. In this paper an attempt was made to develop an optimum cross section of rectangular shaped 3 meter span polymer modified ferrocement roofing/flooring element. The optimum cross section and reinforcement details were arrived using the optimization technique such as simple genetic algorithm (SGA). The detailed experimental investigation on the rectangular shaped polymer modified specimen showed that the polymer modification would improve the characteristics like ultimate load carrying capacity, energy absorption capacity, durability and cracking behaviour, with increase in value of volume fraction of reinforcement.